Regulatory T cells: a promising new therapeutic target in ventricular remodeling after myocardial infarction - Qin, Yiran; Li, Mingxuan; Liu, Haibo (Frontiers in Immunology, 2025)
Myocardial infarction (MI) is one of the leading causes of death worldwide. It is triggered by thrombosis or vascular occlusion. After MI, damaged cardiomyocytes are replaced by scar tissue, leading to systolic and diastolic dysfunction, followed by adverse remodeling. Regulatory T cells (Tregs), as major immune cells, play a crucial role in post-MI inflammation and immunomodulation. Tregs improve cardiac remodeling after MI through various mechanisms, including inhibiting inflammatory cell infiltration, inducing anti-inflammatory macrophages, suppressing cell apoptosis, regulating fibroblast function, and promoting angiogenesis. The modulation of Tregs number or function may provide novel methods for improving post-MI remodeling. This review describes the immunoregulatory roles of Tregs, their regulatory mechanisms in post-MI ventricular remodeling, and the prospects and challenges for clinical application. However, the exact molecular mechanisms of Tregs in ventricular remodeling remain to be investigated. Although most of the current studies are at the preclinical stage, they hold great potential for further application in the future.